2011
DOI: 10.1007/s00360-011-0626-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and mRNA expression of carbamoyl phosphate synthetase III in the liver of the African lungfish, Protopterus annectens, during aestivation or exposure to ammonia

Abstract: This study aimed to obtain the full sequence of carbamoyl phosphate synthetase III (cps III) from, and to determine the mRNA expression of cps III in, the liver of P. annectens during aestivation in air, hypoxia or mud, or exposure to environmental ammonia (100 mmol l(-1) NH(4)Cl). The complete coding cDNA sequence of cps III from the liver of P. annectens consisted of 4530 bp, which coded for 1,510 amino acids with an estimated molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 56 publications
2
22
0
Order By: Relevance
“…As lungfishes are the closest living sister group of land vertebrates, they would logically possess some genes/proteins that are closer to those of other fishes (e.g. carbamoyl phosphate synthetase III, Loong et al, 2012a;argininosuccinate synthase, Chng et al, 2014) and others that have greater similarity to those of tetrapods (e.g. F2 and Fgg, this study; argininosuccinate lyase, Chng et al, 2014; Na + /K + -ATPase α-subunit isoforms, Hiong et al, 2014;L-gulono-γ-lactone oxidase, Ching et al, 2014;betaine-homocysteine Smethyltransferase, Ong et al, 2015).…”
Section: Molecular Characterization Of F2 and Fgg From P Annectensmentioning
confidence: 99%
“…As lungfishes are the closest living sister group of land vertebrates, they would logically possess some genes/proteins that are closer to those of other fishes (e.g. carbamoyl phosphate synthetase III, Loong et al, 2012a;argininosuccinate synthase, Chng et al, 2014) and others that have greater similarity to those of tetrapods (e.g. F2 and Fgg, this study; argininosuccinate lyase, Chng et al, 2014; Na + /K + -ATPase α-subunit isoforms, Hiong et al, 2014;L-gulono-γ-lactone oxidase, Ching et al, 2014;betaine-homocysteine Smethyltransferase, Ong et al, 2015).…”
Section: Molecular Characterization Of F2 and Fgg From P Annectensmentioning
confidence: 99%
“…aethiopicus and P . dolloi possess carbamoyl phosphate synthetase III instead (Chew et al , 2003 a ; Loong et al , 2005, 2012 b , c ), and that the transition of carbamoyl phosphate synthetase III to carbamoyl phosphate synthetase I occurred among amphibians (Ip et al , 2012 c ). Despite being ammonotelic in water, P .…”
Section: Conversion Of Ammonia To a Less Toxic Product For Accumulatimentioning
confidence: 99%
“…Indeed, results from a subsequent study confirmed that environmental ammonia exposure led to a significant increase in the mRNA expression of cps III in the liver of P . annectens , alluding to the important functional role of urea not only as a product of ammonia detoxification but also as an internal signal in the induction of aestivation (Loong et al , 2012 b ).…”
Section: Conversion Of Ammonia To a Less Toxic Product For Accumulatimentioning
confidence: 99%
“…Among the four African species, P. annectens is known to be the most dependent on aestivation; it normally aestivates for periods of 7–8 months in the wild, and a captive lungfish has emerged from its cocoon after periods of up to seven years [3], [4], [5], [6]. Recently, it has been reported that African lungfishes can be induced to aestivate in completely dried mucus cocoon in plastic boxes or in mud cocoon in the laboratory [7], [8], [9], [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Only until very recently, did Loong et al [11], [12] report on the differential gene expression, and the up-regulation of mRNA expression of carbamoyl phosphate synthetase III and ornithine-urea cycle capacity, in the liver of P. annectens during the induction phase (the first 6 days) of aestivation in air. More importantly, there are very few recent studies [13], [14] on the brain of aestivating African lungfish in spite of its possible role in coordinating a whole-body aestivation-specific response during the induction phase of aestivation.…”
Section: Introductionmentioning
confidence: 99%